Emerging Risk Factors for Recurrent Vascular Events in Patients With Embolic Stroke of Undetermined Source. Issue 11 (November 2016) - Ueno, Yuji; Yamashiro, Kazuo; Tanaka, Ryota; Kuroki, Takuma; Hira, Kenichiro; Kurita, Naohide; Urabe, Takao; Hattori, Nobutaka
Abstract : Background and Purpose—: Underlying embolic causes diagnosed by transesophageal echocardiography could be implicated in mechanisms of embolic stroke of undetermined source. We aimed to explore factors, including underlying embolic causes, related to recurrent vascular events in embolic stroke of undetermined source. Methods—: Patients who fulfilled the diagnostic criteria for embolic stroke of undetermined source and whose potential embolic sources were examined by transesophageal echocardiography were included. Recurrent vascular events, including ischemic stroke, cardiovascular and peripheral artery diseases, and vascular death, were retrospectively analyzed. Cox proportional hazards regression analysis was used to explore factors, including clinical characteristics, embolic causes on transesophageal echocardiography, and the Calcification in the Aortic Arch, Age, Multiple Infarction score (CAM), based on the degree of aortic arch calcification on chest radiograph (0–3 points), age (≥70 years; 1 point), and multiple infarctions on magnetic resonance imaging (multiple infarcts in 1, 2, or ≥3 territories of large intracranial arteries, 1, 2, or 3 points) associated with recurrent vascular events. Results—: A total of 177 patients (age, 64.1±14.2 years; 127 men) were enrolled. Thirty-one patients had recurrent vascular events (follow-up, 3.5±2.7 years; annualized rate, 5.0% per person-year). Among embolic causes on transesophageal echocardiography, incidence of recurrent vascular events was high in patients with large aortic arch plaques (7.5% per person-year). Diabetes mellitus (hazard ratio, 2.56; 95% confidence interval, 1.23–5.32; P =0.012) and CAM score grade (hazard ratio, 2.29; 95% confidence interval, 1.11–4.72; P =0.026) predicted recurrent vascular events. Conclusions—: History of diabetes mellitus and the CAM score could be novel risk factors for recurrent vascular events in embolic stroke of undetermined source. Abstract : Supplemental Digital Content is available in the text.